A high efficient graphitic-C3N4/BiOI/graphene oxide ternary nanocomposite heterostructured photocatalyst with graphene oxide as electron transport buffer material. Issue 17 (7th May 2015) - Dai, Kai; Lu, Luhua; Liang, Changhao; Zhu, Guangping; Liu, Qinzhuang; Geng, Lei; He, Junqi
<x xml:space="preserve">Abstract</x> A high efficient graphitic-C3N4/BiOI/graphene oxide ternary nanocomposite photocatalyst with graphene oxide as electron transport buffer material was synthesized.